2007
DOI: 10.3354/dao075251
|View full text |Cite
|
Sign up to set email alerts
|

Conservation in the first internal transcribed spacer region (ITS1) in Hematodinium species infecting crustacean hosts found in the UK and Newfoundland

Abstract: Parasitic dinoflagellates in the genus Hematodinium infect a number of decapod crustaceans in waters off the UK, including the Norway lobster Nephrops norvegicus and the edible crab Cancer pagurus. This study investigated sequence variability in the first internal transcribed spacer (ITS1) region of the ribosomal RNA complex of Hematodinium spp. infecting N. norvegicus, C. pagurus, and Pagurus bernhardus from 4 locations in the UK and from the Hematodinium sp. infecting Chionoecetes opilio from the province of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…In parasitic species like Hematodinium, intra-and inter-individual variation may be confounded if hosts are infected by several genetically differentiated genotypes. Small et al (2007b) found variation only within repetitive regions in ITS1 within Hematodinium isolates from several host species. Because the amplified PCR products in this study were not cloned, it is uncertain whether one or several clones were present in each crab.…”
Section: Hematodinium Spp Cladesmentioning
confidence: 93%
See 2 more Smart Citations
“…In parasitic species like Hematodinium, intra-and inter-individual variation may be confounded if hosts are infected by several genetically differentiated genotypes. Small et al (2007b) found variation only within repetitive regions in ITS1 within Hematodinium isolates from several host species. Because the amplified PCR products in this study were not cloned, it is uncertain whether one or several clones were present in each crab.…”
Section: Hematodinium Spp Cladesmentioning
confidence: 93%
“…Dis Aquat Org 89: [155][156][157][158][159][160][161][162][163][164][165][166] 2010 including Portunus pelagicus, Norway lobsters Nephrops norvegicus and blue crabs Callinectes sapidus (reviewed in Stentiford & Shields 2005, Small et al 2006, 2007b. Despite the potential economic and ecological impact of Hematodinium-related mortality on affected populations, little is known about the method of infection, the life history of the parasite outside the host and the underlying causes for the recent worldwide increase in frequency of Hematodiniumassociated disease.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
See 1 more Smart Citation
“…Different Hematodinium genotypes were related to different host species (Small et al 2007b, Hamilton et al 2010, Jensen et al 2010) and geographical regions (Hamilton et al 2010). It is also clear, however, that a single Hematodinium genotype may infect more than one host species (Hamilton et al 2007, Small et al 2007a, Jensen et al 2010. However, so far only one other species of Hematodinium has been formally described, namely H. australis, which was described on the basis of morphology, host species, and austral location (Hudson & Shields 1994).…”
mentioning
confidence: 99%
“…ITS1 has previously been used to differentiate between closely related Hematodinium spp. infecting a number of hosts (using primers HITS1F and HITS1R also used in the present study, see Small et al 2007a) or confirm a single infective species (Small et al 2007b); if required, it would be possible to use LMD and targeted PCR to amplify further phylogenetically informative regions. This application could be repeated for numerous other aquatic parasites where the diagnostic PCR primers amplify a small fragment.…”
Section: Discussionmentioning
confidence: 99%